Strategi Pemasaran Kreatif Untuk UMKM Es Coklat Melalui Branding Dan Digitalisasi - Septiawan, M. Adib; Pudjoprastyono, Hery (Journal Of Human And Education (JAHE), 2024)
This study discusses the implementation of creative marketing strategies for the Chocolate Ice UMKM in Pakal Village, Surabaya, focusing on branding and digitalization. UMKMs play an important role in the local economy but often face challenges in attracting consumer attention. Through surveys and analyses, we identified the main needs of the UMKM, namely the development of an appealing visual identity and the utilization of digital platforms. The results indicate that creating logos, banners, and ShopeeFood accounts can enhance product visibility and market reach. Training on digital platform usage also equips UMKM actors with the necessary skills to manage online sales effectively. With this strategy, it is hoped that the Chocolate Ice UMKM can compete in an increasingly competitive market and improve their business sustainability.